The Influence of Carbohydrate Metabolism Disorders on the Course of Perioperative Period in Cardiac Surgery Patients with Post-Infarction Left Ventricular Aneurysms - Gogayeva, Olena K. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To study the impact of carbohydrate metabolism disorders on perioperative period in cardiac surgery pa-tients with post-infarction left ventricular (LV) aneurysms. Materials and methods. Retrospective analysis of perioperative period in random 132 patients with post-infarction LV aneurysms of various locations, who were operated on and discharged from the department of surgical treatment of ischemic heart disease of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. Disorders of carbohydrate metabolism (DCM) were detected in 98 (74.2%) patients, among whom type 2 diabetes mellitus (DM) was diagnosed in 34 (25.7%) patients, impaired glucose tolerance (IGT) in 64 (48.5%). All the patients underwent general clinical examination, electrocardiography, echocardiography, coronary angiography and surgical treatment. Results. When analyzing the clinical picture in patients with post-infarction LV aneurysms, painless myocardial isch-emia was diagnosed in 41 (31.06%) patients, among whom type 2 DM in 11 (26.8%) cases and IGT in 18 (43.9%). No statistically significant difference was found in patients with and without DCM in the LV contractile function, presence of LV thrombosis, atrial fibrillation, chronic kidney disease, stenosis of brachiocephalic arteries and arteries of the lower extremities, gouty arthritis, and body weight. Intraoperatively, diameter of the coronary arteries in patients with type 2 DM was slightly smaller compared to patients without DCM. Its increase in cases of calcification of coronary arteries and aorta among patients of the study group with DCM was statistically insignificant. A careful analysis of the postoperative period in patients with and without DCM showed a statistically significant occurrence of paroxysms of atrial fibrillation in 30 (90.9%) and 3 (9.1%) cases, respectively (p=0.0115). The patients with DCM had longer stay in the intensive care unit: 4.03 ± 2.3 vs. 3.2 ± 1.3 days (p=0.0483). Acute kidney injury in the early postoperative period occurred in 8 (6.06%) patients, including 5 (62.5%) with type 2 DM (p=0.0142). Sternal wound infection occurred in 2 (1.5%) patients with type 2 DM (p=0.0156). Conclusions. Among cardiac surgical patients with postinfarction LV aneurysms, the major part is formed by patients with DCM (74.2%), the presence of which complicates the course of the postoperative period with the development of paroxysms of atrial fibrillation (p=0.0115), acute kidney injury (p=0.0142), sternal wound infection (p=0.0156), a long stay in the intensive care unit (p=0.0483).